STRENGTHENING SOCIAL CAPITAL IN IMPLEMENTING SEGORO AMARTO MOVEMENT TO ALLEVIATE POVERTY IN YOGYAKARTA CITY - Lena Satlita; Utami Dewi; Anang Priyanto (Universitas Negeri Yogyakarta, 2017)
This article aims to examine the efforts of stakeholders to strengthen social capital in implementing Segoro Amarto Movement to decrease the number of poverty in Yogyakarta City. The research method of this article was descriptive-qualitative. The data were colected through depth interview, focus group discussion, observation and documentation. The research shows that the implementation of Segoro Amarto Movement Gerakan Segoro Amarto (GSA) had not succeed yet in alleviating poverty in Yogyakarta city since all of actors have not employed social capital well. In strengthening social capital, it needs the mixed between top down and bottom up approach in which the government, community and other stakeholders such as private business, universities and non-governmental organization actively involve in building and enhancing trust, norm and networks to implement Segoro Amarto Movement.Keywords: Segoro Amarto Movement (GSA), social capital, poverty